Zweikomponentige Methoden im Rahmen der zeitabhängigen Dichtefunktionaltheorie - Theorie, Implementierung und Anwendung - Kühn, Michael (KIT Scientific Publishing, 2015)
This book reports on the derivation, implementation and application of two-component methods in the framework of time-dependent density functional theory. These methods allow the calculation of electronic transitions as well as the calculation of the correlation contribution to the electronic ground-state energy (RPA) and to the orbital energies (GW) including spin-orbit coupling. The focus of the applications is put on organic light-emitting diodes and clusters of heavy metals.